Didactic Implications Promoting the Learning of French in Children whit Asperger’s Syndrome - Arellano Calva, Esther (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article presents the results of a case study on the learning of French as a foreign language in a child with Asperger's syndrome. The objective is to highlight the didactic implications that promote this learning in children with this syndrome. We have developed teaching and learning strategies tailored to a 7-year-old child with this autism spectrum disorder, in collaboration with teachers, a neuropsychiatrist, and a psychologist. The interviews conducted and the observations made throughout this research have deepened our understanding of the spectrum, the peculiarities, and the care of these children. This study demonstrates that the implementation of pedagogical strategies and adapted activities can enable children with Asperger's syndrome to communicate with others through the learning of French as a foreign language